Cannabidiol Loaded Topical Ophthalmic Nanoemulsion Lowers Intraocular Pressure in Normotensive Dutch-Belted Rabbits - Samir Senapati; Ahmed Adel Ali Youssef; Corinne Sweeney; Chuntian Cai; Narendar Dudhipala; Soumyajit Majumdar (MDPI AG, 2022)
Cannabidiol (CBD) is the major non-psychoactive and most widely studied of the cannabinoid constituents and has great therapeutic potential in a variety of diseases. However, contradictory reports in the literature with respect to CBD's effect on intraocular pressure (IOP) have raised concerns and halted research exploring its use in ocular therapeutics. Therefore, the current investigation aimed to further evaluate CBD's impact on the IOP in the rabbit model. CBD nanoemulsions, containing Carbopol® 940 NF as a mucoadhesive agent (CBD-NEC), were prepared using hot-homogenization followed by probe sonication. The stability of the formulations post-moist-heat sterilization, in terms of physical and chemical characteristics, was studied for three different storage conditions. The effect of the formulation on the intraocular pressure (IOP) profile in normotensive Dutch Belted male rabbits was then examined. The lead CBD-NEC formulation (1% w/v CBD) exhibited a globule size of 259 ± 2.0 nm, 0.27 ± 0.01 PDI, and 23.2 ± 0.4 cP viscosity, and was physically and chemically stable for one month (last time point tested) at 4 °C, 25 °C, and 40 °C. CBD-NEC significantly lowered the IOP in the treated eyes for up to 360 min, with a peak drop in IOP of 4.5 mmHg observed at the 150 min time point, post-topical application. The IOP of the contralateral eye (untreated) was also observed to be lowered significantly, but the effect lasted up to the 180 min time point only. Overall, topically administered CBD, formulated in a mucoadhesive nanoemulsion formulation, reduced the IOP in the animal model studied. The results support further exploration of CBD as a therapeutic option for various inflammation-based ocular diseases.